RET is a sex-biased regulator of intestinal tumorigenesis - Koester, Sean T.; Li, Naisi; Dey, Neelendu (Frontiers in Gastroenterology, 2024)
Ret is implicated in colorectal cancer (CRC) as both a proto-oncogene and a tumor suppressor. We asked whether RET signaling regulates tumorigenesis in an Apc-deficient preclinical model of CRC. We observed a sex-biased phenotype: ApcMin/+Ret+/- females had significantly greater tumor burden than ApcMin/+Ret+/- males, a phenomenon not seen in ApcMin/+ mice, which had equal distributions by sex. Dysfunctional RET signaling was associated with gene expression changes in diverse tumor signaling pathways in tumors and normal-appearing colon. Sex-biased gene expression differences mirroring tumor phenotypes were seen in 26 genes, including the Apc tumor suppressor gene. Ret and Tlr4 expression were significantly correlated in tumor samples from female but not male ApcMin/+Ret+/- mice. Antibiotics resulted in reduction of tumor burden, inverting the sex-biased phenotype such that microbiota-depleted ApcMin/+Ret+/- males had significantly more tumors than female littermates. Reconstitution of the microbiome rescued the sex-biased phenotype. Our findings suggest that RET represents a sexually dimorphic microbiome-mediated “switch” for regulation of tumorigenesis.